2014
DOI: 10.1155/2014/746874
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Correlation of Oral Lichen Planus and Oral Lichenoid Lesions: A Preliminary Study

Abstract: Oral lichen planus (OLP) and oral lichenoid lesions (OLL) are clinically and histologically similar lesions but their treatment planning and prognosis are different. The review of the literature indicates numerous criteria to distinguish these two lesions; however there is a lot of inconsistency. Thus, the aim of this study was to determine the correlation of histopathology and clinical OLP and OLL diagnosis and to clarify which histopathologic criteria could best distinguish these two diagnoses. A retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 28 publications
(48 reference statements)
5
36
0
3
Order By: Relevance
“…(8) For example, an article by Silverman, 1991, our results may contradict several other studies as stated earlier. (7,12,48) This similarity between allergy rates in OLP and OLL patients found in our study can be explained in three ways.…”
Section: Similarity Between Metal Allergy Rates In Our Olp Group Verssupporting
confidence: 69%
See 4 more Smart Citations
“…(8) For example, an article by Silverman, 1991, our results may contradict several other studies as stated earlier. (7,12,48) This similarity between allergy rates in OLP and OLL patients found in our study can be explained in three ways.…”
Section: Similarity Between Metal Allergy Rates In Our Olp Group Verssupporting
confidence: 69%
“…(7,12) Direct immunofluorescence (DIF) is the best study that oral pathologists have been able to use To obtain a confirmed diagnosis of OLP and to rule out dysplasia or malignancy, a biopsy is necessary.…”
Section: Histological Presentation Of Olpmentioning
confidence: 99%
See 3 more Smart Citations